Breaking Boundaries in the Brain—Advances in Editing Tools for Neurogenetic Disorders - Coorey, Bronte A.; Gold, Wendy A. (Frontiers in Genome Editing, 2021)
Monogenic neurogenetic disorders are devastating, affecting hundreds of millions of people globally and present a substantial burden to individuals, carers and healthcare systems. These disorders are predominantly caused by inherited or de novo mutations that result in impairments to nervous system development, neurodegeneration, or impaired neuronal function. No cure exists for these disorders with many being refractory to medication. However, since monogenic neurological disorders have a single causal factor, they are also excellent targets for innovative, therapies such as gene therapy. Despite this promise, gene transfer therapies are limited in that they are only suitable for neurogenetic disorders that fit within the biological reach of these therapies. The limitations include the size of the coding region of the gene, the regulatory control of expression (dosage sensitivity), the mode of expression (e.g. dominant negative) and access to target cells. Gene editing therapies are an alternative strategy to gene transfer therapy as they have the potential of overcoming some of these hurdles, enabling the retention of physiological expression of the gene and offers precision medicine-based therapies where individual variants can be repaired. This mini review focusses on the existing gene editing technologies for neurogenetic disorders and how these propose to overcome the challenges common to neurogenetic disorders with gene transfer therapies as well as their own challenges.